Analysis of magnetohydrodynamic partial slip laser bump texture slider and journal bearing. (December 2019) - Rao, TVVLN; Rani, Ahmad Majdi Abdul; Mohamed, Norani Muti; Ya, Hamdan Haji; Awang, Mokhtar; Hashim, Fakhruldin Mohd
A model of magnetohydrodynamic partial slip laser texture bearing (slider and journal) is developed. The influence of laser bump texture and slip laser texture partial configuration on the magnetohydrodynamic performance analysis of bearing is presented. An electrically conducting fluid is confined to bearing surfaces under uniform magnetic field perpendicular to slider bearing and inclined to the line of maximum film thickness to journal bearing. A one-dimensional analysis based on the narrow groove theory is considered to evaluate the nondimensional pressure distribution in bearing. Results of the nondimensional load capacity and coefficient of friction of magnetohydrodynamic partial laser bump texture and partial slip laser texture bearing configurations are analyzed. Partial slip configuration under MHD lubrication without laser bump texture brings in the performance improvement.